Analysis of MGs with Strongly Independent and Weakly Independent Places Using Sign Incidence Matrix and Their Conversion into Directed graphs - Balaji P, Ravikumar R (International Journal of Advanced Science and Technology, 2020)
In this paper in the beginning introduction to PT net (Place –transition net) is given.  Basic notations and formal definition are given. Finally a MG (Marked Graph) with strongly independent and weakly independent places is taken and analyzed using sign incidence matrix for finding set of places which are both S & T.(Siphon and Trap)  Also the MG is converted into directed graphs by three methods. Then the directed graphs are analyzed.